Hybrid Solar Energy System as Alternative Power Supply in Mindanao State University-Sulu: Impact on Quality Services - BusaÃ±a, Maryjoy A. (Open Access Indonesia Journal of Social Sciences, 2021)
To ascertain the hybrid solar energy system as alternative power supply in Mindanao State University-Sulu and its impact to quality service, This study aims to investigate the extent of benefits of hybrid solar power in terms of a) cost, b) availability, and c.)sustainability, moreover, it also investigate its preferability of hybrid solar power over traditional electricity, while it identifies the significant impact of Hybrid Solar power as a source of power supply to the quality of service of MSU-Sulu Administration, significant correlation between the preferability level and the impact of Hybrid Solar power. The quantitative data was analysed and interpreted using statistical tools weighted arithmetic mean and correlation and for qualitative data which is the interview, thematic analysis was utilized. The researcher was able to analyzed the gathered data through Mix Method for the preferability of hybrid solar power over traditional electricity and hybrid solar power its impact to quality service were obtained. The respondents of this study were the forty eight (48) teaching personnel and thirty eight (38) non-teaching personnel and an expert on solar panels. Purposive and random Sampling was used in the selection of the respondents. The instruments of the study were Guided Interview Questions and survey questionnaire. The qualitative data were obtained from the interview by the expert on solar panels. The quantitative data checklist questionnaire were obtained personally by the researcher and validated by three (3) Experts. The study revealed that the use of hybrid solar energy system as an alternative power supply has an impact to the quality service of Mindanao State University-Sulu, thus, both teaching and non-teaching personnel preferred the use of Hybrid solar energy system over traditional electricity. The extent of benefits of hybrid solar power in term costs is feasible for the costs of its installation will be treated as an investment for its 5 or more years of use of its naturally free electric power supply. In the long run, the Hybrid Solar energy will ensure a return of investment in its electric consumption. In terms of availability, it is guaranteed available by the partner company and in terms of its sustainability, it can support the entire university for 5 year’s or more with quality solar equipment that it turns, the university will be able to provide quality service to its clientele. Hence, the following are the recommendations of the study. on research agenda, the school administrator should consider this study as beneficial to the school, the adaption of the Hybrid Solar Energy power to the electric supply of the Mindanao State University-Sulu, Quality service entails the need of uninterrupted power supply and this hybrid solar energy power is the solution, and Quality service rendered by both teaching and non-teaching personnel would be maximized with the help of this hybrid power energy system. On this note, the following are the recommended policy: School administrator must look into ways on the adaptation of the hybrid power energy system into the university, Rigorous planning and careful assessment on the applicability of hybrid solar energy power on each college as well as administrative offices, pioneered application among key services provider of the university like registrar and cashier’s office, gradual use of hybrid Solar Energy power among colleges, mainly on the enrolment process to the releasing of grades, and School administrator should conduct a seminar to its constituents on the cognizance on the benefits of using solar power and raising an awareness on how to conserve Energy and use it in a proper way.